Congenital Cystic Lung Lesions: Evolution From In-utero Detection to Pathology Diagnosis—A Multidisciplinary Approach. (September 2017) - Hardee, Steven; Tuzovic, Lea; Silva, Cicero T; Cowles, Robert A; Copel, Joshua; Morotti, Raffaella A
Congenital cystic lung lesions are a group of rare pathologies that are usually diagnosed in the prenatal period. The majority of these lesions are diagnosed at pathology examination as congenital pulmonary airway malformations (CPAM) and bronchopulmonary sequestration (BPS). These lesions are typically managed by surgical intervention within the first year of life and have an excellent prognosis. We examined the evolution of imaging appearances from prenatal diagnosis to postnatal work-up of these lesions and correlate imaging and pathological findings. An 8-year retrospective review of the perinatal and pathology database of a single tertiary care center identified 42 cases of congenital cystic lung lesions of which 36 had known prenatal ultrasound and prenatal course available. Final pathologic diagnoses were 15 CPAM (41%), 7 BPS (19%), and 9 hybrid BPS and CPAM lesions (25%). Five cases with bronchial atresia were also identified (either in isolation or associated with CPAM or BPS). The overall characteristics of these lesions by prenatal ultrasound, postnatal imaging, and ultimate histopathologic diagnosis are described.